Analysis of rainfall for strategic crop planning under rainfed rice based cropping system in Chhattisgarh - Chaudhary, J.L.; Sinha, Neha; Patel, S.R.; Khavse, Rajesh; Manikandan, N. (Annals of Agricultural Research, 2016)
Chhattisgarh state located in central India covers total area of about 13.5 million hectares. The region has a great variety and diversity of weather conditions. Three major agro-climatic zones has been demarcated in the state viz., Chhattisgarh plains zone, Bastar plateau ACZ and Northern hill region. Here an analysis of rainfall for some representative districts has been made and interpretation drawn regarding pre-dominant crop rice cultivation. On observation it has been found that the annual rainfall decreases from east to west. The annual rainfall in the eastern part of the state varies from 1300-1600 mm. This covers Mahasamund, Raipur, Janjgir, Korba, Raigarh, Jashpur and Surguja districts. On examining the CV for the annual rainfall, it has been found to be the least at Bilaspur followed by Jagdalpur, Raipur and Ambikapur. Similarly the dependable rainfall quantity and periods have been calculated. Farm tanks and OFRs can be developed to preserve surplus water to optimize its use not only for rice crop as life saving irrigation but also for succeeding crop and make an effort for increasing cropping intensity.